The impact of biofuels for road traffic on air quality : a modelling approach - Ribeiro, Isabel Lavrador (2015)
The selection of the energy source to power the transport sector is one of the main current concerns, not only relative with the energy paradigm but also due to the strong influence of road traffic in urban areas, which highly affects human exposure to air pollutants and human health and quality of life. Due to current important technical limitations of advanced energy sources for transportation purposes, biofuels are seen as an alternative way to power the world’s motor vehicles in a near-future, helping to reduce GHG emissions while at the same time stimulating rural development. Motivated by European strategies, Portugal, has been betting on biofuels to meet the Directive 2009/28/CE goals for road transports using biofuels, especially biodiesel, even though, there is unawareness regarding its impacts on air quality. In this sense, this work intends to clarify this issue by trying to answer the following question: can biodiesel use contribute to a better air quality over Portugal, particularly over urban areas? The first step of this work consisted on the characterization of the national biodiesel supply chain, which allows verifying that the biodiesel chain has problems of sustainability as it depends on raw materials importation, therefore not contributing to reduce the external energy dependence. Next, atmospheric pollutant emissions and air quality impacts associated to the biodiesel use on road transports were assessed, over Portugal and in particular over the Porto urban area, making use of the WRF-EURAD mesoscale numerical modelling system. For that, two emission scenarios were defined: a reference situation without biodiesel use and a scenario reflecting the use of a B20 fuel. Through the comparison of both scenarios, it was verified that the use of B20 fuels helps in controlling air pollution, promoting reductions on PM10, PM2.5, CO and total NMVOC concentrations. It was also verified that NO2 concentrations decrease over the mainland Portugal, but increase in the Porto urban area, as well as formaldehyde, acetaldehyde and acrolein emissions in the both case studies. However, the use of pure diesel is more injurious for human health due to its dominant VOC which have higher chronic hazard quotients and hazard indices when compared to B20.